Master-controlled networking for mobile robotics application - Lee, Chin Bin (2024)
The goal of this project is to establish a master-controlled networking system for mobile robotics applications. It addresses problems and offers methods, hardware, and software solutions. This project will be built on top of the GoPiGo3 platform, which has many robots set up as slaves and one robot designated as the master. The slave robots will be outfitted with object storage, while the master robot will get changes, including the installation of an arm. These changes are mostly intended to simulate a warehouse environment, in which items are dispersed and not particularly arranged. The GoPiGo3 robots will link their arms and sensors to enable communication and cooperation. Dedicated mobile apps will be available for both the master and slave robots. These apps will come with a range of functionality, including as arm control, camera operations, and robot navigation, all of which are intended to provide users a thorough grasp of the robot's capabilities and enable easier control. Java will be used in Android Studio to construct the mobile apps. Local area network (LAN) and master-slave communication will be used in tandem to facilitate communication between the master and slave robots. After processing orders or data, the master robot will provide the required information to the slave robots. In this situation, when communication is necessary for coordinated actions and reactions, the master might be compared to a commander and the slaves to troops.